2022
DOI: 10.1111/eci.13900
|View full text |Cite
|
Sign up to set email alerts
|

Serum proprotein convertase subtilisin/Kexin type 9 and vascular disease in type 2 diabetic patients

Abstract: Background Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) levels have been suggested as novel atherosclerotic biomarker. PCSK9 plays important roles in the pathogenesis of atherosclerosis by regulating the degradation of low‐density lipoprotein receptor as well as different inflammatory pathways. Considering the important prognostic role of arterial stiffness in cardiovascular disease (CVD), the aim of the study is to investigate the correlation between PCSK9 levels and arterial stiffness in a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In our study, in a group of Chinese Han T2DM patients, the plasma level of PCSK9 was positively correlated with the severity of coronary heart disease, as shown by the linear correlation results (diseased vessels: r = 0.35, p < 0.001; GS: r = 0.46, p < 0.001, significantly). To date, only Armentaro et al have reported similar results in Caucasian populations [20]. It is important to emphasize how the genetic background affects clinical outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our study, in a group of Chinese Han T2DM patients, the plasma level of PCSK9 was positively correlated with the severity of coronary heart disease, as shown by the linear correlation results (diseased vessels: r = 0.35, p < 0.001; GS: r = 0.46, p < 0.001, significantly). To date, only Armentaro et al have reported similar results in Caucasian populations [20]. It is important to emphasize how the genetic background affects clinical outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…To explore the relationship between PCSK9 and CHD severity, we divided the patients in the CHD group into four subgroups based on the quartile of PCSK9 levels (Supplementary Table 1). We observed that the percentage of patients with three-vessel disease (17.30% vs. 31.01% vs. 50.45% vs. 66.52%, p < 0.001) and GS [23 (21) vs. 30 (21) vs. 36 (24) vs. 46 (20), p < 0.001] increased in the high PCSK9 group, whereas the percentage of patients with one-vessel disease decreased (p < 0.001), indicating that PCSK9 levels may be associated with CHD severity. Furthermore, Spearman's correlation analysis showed that serum PCSK9 levels were significantly and positively associated with diseased vessels and GS (r = 0.35, p < 0.001; r = 0.46, p < 0.001, respectively) (Fig.…”
Section: Association Between Pcsk9 and The Severity Of Chdmentioning
confidence: 90%
See 2 more Smart Citations